Answer:
y= = -3x -11
STANDARD FORM: 3x+y= -11
Step-by-step explanation:
15 + 2x - 4 = 9x + 11 - 7x
2x + 11 = 2x + 11
always true
2x + 3(4x - 1) = 2(5x + 3) + 4x
2x + 12x - 3 = 10x + 6 + 4x
14x - 3 = 14x + 6
never true
Answer:
a(n) = -16b + (n - 1)(3b)
Step-by-step explanation:
First term is -6b.
Common difference is 3b; each new term is equal to the previous one, plus 3b.
Formula for this arithmetic sequence is
a(n) = -16b + (n - 1)(3b)
2/9+5/6 in simplest form is 1 1/18
Hope this helped :P
Answer:
is there a picture?
Step-by-step explanation: